2017
DOI: 10.1186/s40880-017-0203-x
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of E-cadherin enhances prostate cancer chemoresistance via Notch signaling

Abstract: BackgroundThe chemoresistance of prostate cancer (PCa) is invariably associated with the aggressiveness and metastasis of this disease. New emerging evidence indicates that the epithelial-to-mesenchymal transition (EMT) may play pivotal roles in the development of chemoresistance and metastasis. As a hallmark of EMT, E-cadherin is suggested to be a key marker in the development of chemoresistance. However, the molecular mechanisms underlying PCa chemoresistance remain unclear. The current study aimed to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 43 publications
7
50
0
Order By: Relevance
“…EMT-related transcription factors such as Snail, Slug and Twist are shown to confer chemo-resistance in ovarian, breast and nasopharyngeal carcinoma [ 18 , 19 , 20 ]. In PCa, a study demonstrated that reintroduction of E-cadherin significantly sensitizes chemo-resistant PCa cell lines to paclitaxel [ 21 ]. A recent study showed that Skp2-mediated Twist stabilization can facilitate the acquisition of chemo-resistant to paclitaxel or doxorubicin during PCa progression toward CRPC [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…EMT-related transcription factors such as Snail, Slug and Twist are shown to confer chemo-resistance in ovarian, breast and nasopharyngeal carcinoma [ 18 , 19 , 20 ]. In PCa, a study demonstrated that reintroduction of E-cadherin significantly sensitizes chemo-resistant PCa cell lines to paclitaxel [ 21 ]. A recent study showed that Skp2-mediated Twist stabilization can facilitate the acquisition of chemo-resistant to paclitaxel or doxorubicin during PCa progression toward CRPC [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that Snail and E‐cadherin, markers of EMT, induce chemoresistance . Thus, we examined the expression of Snail and E‐cadherin in KYSE70, KYSE70‐siHOXA13, KYSE510, and KYSE510‐HOXA13.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that downregulation of claudin-1 did not affect EMT in prostate epithelial cells. Other studies have shown that claudin-1 overexpression is evident in prostate cancer,30 and that overexpression of E-cadherin (which was not altered by claudin-1 knockdown) downregulated claudin-1 and inhibited tumor cell migration and invasion 31. Our studies suggest that in BPH, which is not associated with prostate carcinogenesis, claudin-1 expression is decreased-and thus our experiments focused on the functional consequences of claudin-1 downregulation and the potential impact of TGF-β1 signaling on the epithelial barrier.…”
mentioning
confidence: 88%